Broadband connectivity, government policies, and open innovation: The crucial it infrastructure contribution in Scotland - Sayed Abdul Majid Gilani; Alessio Faccia (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Broadband connectivity is now essential to ensure a competitive advantage for any business. The analysis of Scotland's crucial IT infrastructure contribution supported the authors' thesis that the Government plays a decisive role in Open Innovation ecosystems. Indeed, IT infrastructures are a clear case of market failure where remote areas will never be served by adequate connectivity without public support. The main contribution is the demonstration that the benefits of public intervention are sometimes required and beneficial to correct market distortions and generate positive spillovers in terms of collaboration in Open Innovation ecosystems. Another relevant contribution is a comprehensive analysis of the consistency of the evolution of the public policies that supported the IT Infrastructure in Scotland. Therefore, pivotal is the study of this case study that can be easily generalised to many other contexts where the Government addressed market failures and, at the same time, contributed to generating collaborative environments.
Keywords: 650; broadband connectivity; government policies; open innovation; Scotland